Critical Analysis of Public Health Strategies, Behavioral Health, and System Sustainability - Almahfod, Waleed Zaidan; Garmoush, Ali Abdullah saeid; Al Farwan, Majed Saleh Adbullah; Alaghtani, muhammd Abdullah Saleh; Alabood, Mohammed Jaffar Mohammed; AL hammad, Saad Aboud Mohammed; Alshrani, Nourah Mohammed Ali; Al haydar, Mana Abdullah Salem; Al-Munajjim, Ali Hanish Abdullah; Alhaidar, Abdullah Fisal Ahmad (Journal of Ecohumanism, 2024)
Systematic approaches, behavioral health initiatives, and improving the sustainability of systems on which health reformers rely form the fundamentals of resolving various public health issues of the 21st century. This paper critically discusses historical developments of public health policies and practices, the effectiveness of the policies on behavioral health, and the sustainability of health systems in relation to current trends and future perspectives. As an interdisciplinary tool, it assesses how policies, communities, and technologies intertwine by presenting empirical evidence and a set of case outcomes. Specific findings suggest room for using integrated systems-based approaches that are amenable to scale and that support population health improvement within environmental, economic, and social contexts to address health inequities. The solutions are focused on increasing the priority of outpatient services, developing behavioral health, and implementing sustainable solutions.